UPAYA MENINGKATKAN MOTIVASI BELAJAR SEJARAH KEBUDAYAAN ISLAM MELALUI MODEL TEAM GAMES TOURNAMENT (TGT) PADA SISWA KELAS X MA Al-Ahliyah - Lulu Nurlaila; Solihah Bagus; Usep Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The teaching of history until now still largely uses traditional learning methods, whether through lectures or explanations. In history lessons that merely present material through lectures, it is felt to be less effective, as students find it difficult to understand and grasp the material. The research on the Application of the Cooperative Learning Model Teams Games Tournament (TGT) in Improving Motivation and Learning Outcomes in Islamic Cultural History for 10th Grade Students at MA Al-Ahliyah is a Classroom Action Research aimed at determining the increase in motivation and learning outcomes of 10th grade students at MA Al-Ahliyah after implementing the Cooperative Learning model Teams Games Tournament (TGT). The subjects of this research are 26 10th grade students at MA Al-Ahliyah, consisting of 9 male students and 17 female students. This research was conducted in 2 cycles, with 3 meetings in each cycle through 4 stages, namely: (1) action planning; (2) action implementation; (3) action observation. The results of the research related to student learning outcomes indicate that before the implementation of the TGT learning model, the average student learning outcomes were in the very low category. In cycle 1, the average student learning outcomes were in the low category. And in cycle II, the average student learning outcomes were in the high category. Based on these research results, it can be concluded that the application of the Cooperative Teams Games Tournament (TGT) learning model can improve the motivation and learning outcomes of history students in class X MA Al-Ahliyah.